EMPOWERING INCLUSIVE CLASSROOMS: INTEGRATING TECHNOLOGY INTO ENGLISH LANGUAGE TEACHING THROUGH PRACTICAL TOOLS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Integrating technology, such as ChatGPT, Quizlet, and Kahoot, into English language teaching significantly enhances learner engagement and performance in inclusive classrooms. This paper explores the practical implementation of digital tools in Uzbek schools, involving 3 teachers and 15 students. The study analyzes improvements in vocabulary acquisition, motivation, and speaking fluency using AI-driven and interactive platforms. Findings show that purposeful technological integration benefits all learners, especially in diverse educational settings.